JOURNALISM IN THE DIGITAL AGE - CHALLENGES AND SOLUTIONS FOR TRAINING WORK - Vu Thi Phuong Le (Tạp chí Khoa học)
The vigorous development of the Fourth Industrial Revolution has brought humanity into the digital age. Journalism and journalism training in Vietnam are facing many new problems; advantages and opportunities are intertwined with difficulties and challenges. In this article, based on the synthesis of theoretical and practical sources in Vietnam, we analyze the opportunities that the digital age brings to journalism and also point out the challenges journalism human resource training faces in the digital age. We also propose appropriate solutions for journalism human resource training to meet new requirements in the context of the digital age.